Trânsito religioso: um estudo de caso em uma igreja pentecostal de Goiânia, Goiás - Jesus, Welton Lourenço Calháo de (2016)
The religious transit, understood as the flow of people, beliefs and practices of religious institutions, constitutes a phenomenon intensified in postmodernity. Individuals, exercising their autonomy to choose their religious symbolic universe, it is assumed subject of faith itself, independently of religious bodies. These, in turn, set in a plural and competitive religious field, seek to maintain its plausibility and relevance. In this context, there is the establishment of the logic of a religious economy, under which it gives a dialectical relationship between religious institutions, as providers of religious symbolic goods, and individuals as plaintiffs. The question problem approched in this essay refers to the reasons that lead people to change religions, cults or churches. The hypothesis made is that people move pragmatically between religious institutions in the pursuit of the satisfaction of needs of everyday life. Secondary research was conducted in bibliographies of religious studies, as well as an empirical case study in a Pentecostal church in Goiânia /GO, which involved religious leaders and goers. The objectives of this study were to identify the prevalent reasons for the religious transit, identify the religious groups involved, know the profile of the people who made the traffic, identify ejector factors of their home churches as well as know the attractor factors to the current religious institution. The results confirmed the hypothesis. Among the main prevalent reasons identified, there is a change of address/location. As for the main ejector factors identified, stands out the "disagreement with teaching, standards and/or practices of the church" and "relationship problems/disappointment with brothers and/or leaders." As for the main attractor factors, the most suitable were the "quality of relationships between people" and the "influence of friends and family”. The Catholic Church was the religious institution that gave more followers, but were Evangelicals, as one of the major religious groups (according to the classification of the IBGE), from which originated most of the traffic. Most of the people who practiced religious transit is female, married, working with a formal contract with income between 1 and 3 minimum wages, born in Goiânia/GO, attends the main programs of the church, takes part of the church for more than 3 years and is recognized as a member of the church.